“Masato de Yuca” and “Chicha de Siete Semillas” Two Traditional Vegetable Fermented Beverages from Peru as Source for the Isolation of Potential Probiotic Bacteria - Rebaza-Cardenas T.D. (2021)
Open Access funding provided thanks to the CRUE-CSIC agreement with Springer Nature. This research was funded by the Ibero-American Programme on Science and Technology for Development (CYTED), grant number 917PTE0537. The Spanish team was funded by the “Agencia Estatal de Investigación” and the “Fondo Europeo de Desarrollo Regional” (AEI/FEDER, UE), grant number PCIN2017-075″. The Peruvian team was funded by the National Council of Science and Technology and Innovation of Peru through its execution unit National Fund for Scientific, Technological and Technological Innovation (CONCYTEC/FONDECYT), grant No. 001–2017.